EVALUATING THE INTERNET - Lehmann, Susan; Schultz, Norah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this exercise is to gain experience locating information on the internetand gauging its reliability. This exercise is crucial before beginning any of the otherexercises in the book. You will be directed to find your university’s site, or another sitecreated by a university library system, that presents some guidelines for judging thequality of different information sources. The exercise will then guide you through theprocess of evaluating the various types of sites put on the internet by governments,universities, and other organizations.